Analisis kepuasan Taruna Poltekbang Medan menggunaka Metode QFD (Quality Function Devopment) - Hutabarat, Liber Tommy; Pangaribuan, Lisda Juliana (Politeknik Ganesha Medan, 2020)
Education is an important factor in the development of science and the technology. Quality of service is an important element in the institution of education for the quality service of education that will produce high-quality graduates as well. The importance of service quality makes it a part of the Higher Education Quality Standards. Cadets Satisfaction to services is a benchmark to find out the quality of service at Medan Aviation Polytechnic. This research aims to determine the level of Cadets satisfaction to Medan Aviation Polytechnic service towards learning management standard services and standards for infrastructure facilities. The results of the study will be used as references in developing quality standards of Medan Aviation Polytechnic. The method used was Quality Function Deployment (QFD) method, with a total sample of 44 people. Analysis of the data is done with test validity, reliability, planning matrices and matrix House of Quality (HOQ). Analysis results shows the level of cadets satisfaction highest is the dimension Realibility to value the satisfaction of 4.01 followed by the dimensions of Assurance with the value of the satisfaction of 3.98, then the dimension Empaty to value the satisfaction of 3.97 and then at Responsivness dimension with satisfaction value 3.95 and the last is Tangibility dimension with satisfaction value 3.92.